Perceived and actual physical literacy and physical activity: A test of reverse pathway among Hong Kong children - Ming Hui Li; Raymond Kim Wai Sum; Cindy Hui Ping Sit; Yong Liu; Ru Li (Elsevier, 2021)
Background/objective: The directional relationship between physical literacy (PL) and physical activity (PA) in children remains unclear. This study explored the directionality of the relationship between children's actual PL and PA, and whether their PL perceptions mediate this relationship. Methods: This was a cross-sectional study. In total, 371 children (153 boys; Mage = 10.0 ± 1.0) from Chinese primary schools were recruited to complete all the assessments. Structural equation modeling (SEM) was conducted to determine a reciprocal relationship between Motivation and Confidence, Daily Behavior and moderate-to vigorous-intensity physical activity (MVPA). Results: When perceived PL was examined as a mediator, the model with direction from MVPA to actual PL was observed with significance in Motivation and Confidence (β = 0.48) and Daily Behavior (β = 0.20). Perceived PL displayed no mediation effect for the direction from actual PL to MVPA. Conclusions: This study provides evidence that engagement in PA might be useful to support the continuous development of PL. As perceived PL is an integral part of this relationship, future research is needed to understand its role for providing potential intervention targets to improve these outcomes among Chinese children.